TLR4 mutations (Asp299Gly and Thr399Ile) are not associated with ankylosing spondylitis. Issue 8 (12th July 2006) - Adam, R; Sturrock, R D; Gracie, J A
Abstract : Background: Immunoregulatory genes and Gram negative gut bacteria are thought to be important in disease expression in ankylosing spondylitis (AS). Objective: To compare the frequency of two common and functional TLR4 mutations (Asp299Gly, and Thr399Ile) between patients with AS and HLA-B27 healthy controls. Methods: The TLR4 genotypes of patients and healthy HLA-B27 controls were determined using allele-specific PCR and restriction fragment length polymorphism analysis. Asp299Gly genotype was determined in 193 patients and 125 HLA-B27 positive controls and Thr399Ile genotype in 184 patients and 113 HLA-B27 controls. Allele frequencies were compared using a χ 2 test of association. Results: 29/193 (15%) patients with AS had a polymorphism in the Asp299 site compared with 18/125 (14.4%) healthy HLA-B27 controls. Of the patients genotyped for the Thr399Ile allele, 29/184 (15.8%) carried the polymorphism compared with 19/113 (16.8%) HLA-B27 controls. No significant difference between the frequencies of the Asp299Gly genotype or the Thr399Ile genotype between patients with AS and healthy HLA-B27 controls was found. No significant difference in allele frequency was found at either site. Conclusion: Two common TLR4 polymorphisms, which cause a functional deficiency in host immune response to Gram negative bacteria, are not overrepresented in patients with AS.